1995
DOI: 10.1037/0022-3514.69.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Does the Defining Issues Test measure psychological phenomena distinct from verbal ability? An examination of Lykken's query.

Abstract: This study examined the incremental validity of the Denning Issues Test (DIT), a test purporting to measure moral reasoning ability relative to verbal ability and other major markers of the construct of general intelligence (g). Across 2 independent studies of intellectually precocious adolescents (top 0.5%), results obtained with the DIT revealed that gifted individuals earned significantly higher moral reasoning scores than did their average-ability peers; they also scored higher than college freshmen, who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 58 publications
2
96
2
1
Order By: Relevance
“…(p. 191) Similarly, Lykken (1991) wrote, "One can reasonably wonder whether many of the interesting findings obtained in research on Kohlberg's Stages of Moral Development would remain if verbal intelligence had been partialed out in each case" (p. 35). Sanders, Lubinski, and Benbow (1995) tested the latter hypothesis and found that scores on the Defining Issues Test were unrelated to 62 criterion variables after partialing out the effects of verbal ability, a finding that prompted the following speculation:…”
Section: Discussionmentioning
confidence: 99%
“…(p. 191) Similarly, Lykken (1991) wrote, "One can reasonably wonder whether many of the interesting findings obtained in research on Kohlberg's Stages of Moral Development would remain if verbal intelligence had been partialed out in each case" (p. 35). Sanders, Lubinski, and Benbow (1995) tested the latter hypothesis and found that scores on the Defining Issues Test were unrelated to 62 criterion variables after partialing out the effects of verbal ability, a finding that prompted the following speculation:…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that some innovative constructs that make intuitive sense have frequently failed to add value when compared with preexisting measures (e.g., Sanders, Lubinski, & Benbow, 1995 (Jitendra & Kameenui, 1993). If DA does not add a significant amount of information to the existing measures in explaining students' academic performance, the benefits of DA may not outweigh its costs.…”
Section: Two Challenges In Dynamic Assessment Researchmentioning
confidence: 99%
“…Informed by the theories about multiple intelligences we previously discussed (Bailey & Morley, 2006;Major, Johnson & Deary, 2012), we identify a wide range of multifaceted and domain-specific ability tests designed to capture specific innate abilities, that can be applied in talent-identification procedures (see Table 1) such as WISC-R, the Wechsler Individual Achievement Test, and the Self-Regulation and Concentration Test (Bianco, 2010;Sanders, Lubinski & Benbow, 1995;Saccuzzo & Johnson, 1995: Periathiruvadi & Rinn, 2012Preckel & Tiemann, 2003). These tests are frequently combined with subjective judgments collected through supervisor, peer, and self-evaluation (Bailey & Morley, 2006;Baldwin, 2005).…”
Section: Ability Componentmentioning
confidence: 99%